Robust Semi-Discrete and Fully Discrete Hybrid Stress Finite Element Methods for Elastodynamic Problems (Advances in Applied Mathematics and Mechanics, 2018)
This paper analyzes semi-discrete and fully discrete hybrid stress quadrilateralfinite element methods for 2-dimensional linear elastodynamic problems. Themethods use a 4-node hybrid stress quadrilateral element in the space discretization.In the fully discrete scheme, an implicit second-order scheme is adopted in the timediscretization. We derive optimal a priori error estimates for the two schemes andan unconditional stability result for the fully discrete scheme. Numerical experimentsconfirm the theoretical results.